ChemInform Abstract: Flow Synthesis of Substituted γ‐Lactones by Consecutive Photocatalytic/Reductive Reactions. Issue 35 (2nd September 2014) - Fagnoni, Maurizio; Bonassi, Filippo; Palmieri, Alessandro; Protti, Stefano; Ravelli, Davide; Ballini, Roberto
Abstract Photolytic addition reaction of aldehydes to activated alkenes and subsequent reduction with hydride under continuous flow reaction conditions provides multisubstituted γ‐lactones as mixtures of diastereomers.